Gut–liver axis and sterile signals in the development of alcoholic liver disease. (8th May 2017) - Szabo, Gyongyi; Petrasek, Jan
Abstract: Background: Innate immunity plays a critical role in the development of alcohol-induced liver inflammation. Understanding the inter-relationship of signals from within and outside of the liver that trigger liver inflammation is pivotal for development of novel therapeutic targets of alcoholic liver disease (ALD). Aim: The aim of this paper is to review recent advances in the field of alcohol-induced liver inflammation. Methods: A detailed literature review was performed using the PubMed database published between January 1980 and December 2016. Results: We provide an update on the role of intestinal microbiome, metabolome and the gut–liver axis in ALD, discuss the growing body of evidence on the diversity of liver macrophages and their differential contribution to alcohol-induced liver inflammation, and highlight the crucial role of inflammasomes in integration of inflammatory signals in ALD. Studies to date have identified a multitude of new therapeutic targets, some of which are currently being tested in patients with severe alcoholic hepatitis. These treatments aim to strengthen the intestinal barrier, ameliorate liver inflammation and augment hepatocyte regeneration. Conclusion: Given the complexity of inflammation in ALD, multiple pathobiological mechanisms may need to be targeted at the same time as it seems unlikely that there is a single dominant pathogenic pathway in ALD that would be easily targeted using a single target drug approach. Short summary: Here, we focus on recent advances in immunopathogenesis of alcoholic liver disease (ALD), including gut–liver axis, hepatic macrophage activation, sterile inflammation and synergy between bacterial and sterile signals. We propose a multiple parallel hit model of inflammation in ALD and discuss its implications for clinical trials in alcoholic hepatitis.